Plasma Enabled Conformal and Damage Free Encapsulation of Fragile Molecular Matter: from Surface‐Supported to On‐Device Nanostructures. (8th July 2019) - Alcaire, Maria; Aparicio, Francisco J.; Obrero, José; López‐Santos, Carmen; Garcia‐Garcia, Francisco J.; Sánchez‐Valencia, Juan R.; Frutos, Fabián; Ostrikov, Kostya (Ken); Borrás, Ana; Barranco, Angel
Abstract: Damage‐free encapsulation of molecular structures with functional nanolayers is crucial to protect nanodevices from environmental exposure. With nanoscale electronic, optoelectronic, photonic, sensing, and other nanodevices based on atomically thin and fragile organic matter shrinking in size, it becomes increasingly challenging to develop nanoencapsulation that is simultaneously conformal at atomic scale and does not damage fragile molecular networks, while delivering added device functionality. This work presents an effective, plasma‐enabled, potentially universal approach to produce highly conformal multifunctional organic films to encapsulate atomically thin graphene layers and metalorganic nanowires, without affecting their molecular structure and atomic bonding. Deposition of adamantane precursor and gentle remote plasma chemical vapor deposition are synergized to assemble molecular fragments and cage‐like building blocks and completely encapsulate not only the molecular structures, but also the growth substrates and device elements upon nanowire integration. The films are insulating, transparent, and conformal at sub‐nanometer scale even on near‐tip high‐curvature areas of high‐aspect‐ratio nanowires. The encapsulated structures are multifunctional and provide effective electric isolation, chemical and environmental protection, and transparency in the near‐UV–visible–near‐infrared range. This single‐step, solvent‐free remote‐plasma approach preserves and guides molecular building blocks thus opening new avenues for precise, atomically conformal nanofabrication of fragile nanoscale matter with multiple functionalities. Abstract : An effective and generic approach for highly conformal nanopackaging of fragile nanoscale functionalities of interest to diverse applications is presented. Transparent low‐k insulators that are robust in corrosive environments are fabricated by remote plasma deposition of adamantane. These organic nanocoatings are applicable to a broad range of materials beyond the demonstrated encapsulation of graphene monolayers and conducting π‐stacked molecular nanowires.